Modeling and projecting implosion performance for the National Ignition Facility. (18th December 2018) - Clark, D.S.; Weber, C.R.; Kritcher, A.L.; Milovich, J.L.; Patel, P.K.; Haan, S.W.; Hammel, B.A.; Koning, J.M.; Marinak, M.M.; Patel, M.V.; Schroeder, C.R.; Sepke, S.M.; et al.
Abstract: Steady progress is being made in inertial confinement fusion experiments at the National Ignition Facility (NIF). Nonetheless, substantial further progress is still needed to reach the ultimate goal of fusion ignition. Closing the remaining gap will require either improving the quality of current implosions, increasing the implosion scale (and correspondingly the energy delivered by NIF), or some combination of the two. But how much of an improvement in implosion quality or energy scale is required to reach ignition? To reliably answer this question, an accurate understanding of current and past experiments is first required. Previous modeling efforts of NIF implosions have shown the need to resolve a wide range of scales (from microns to millimeters) as well as a faithful representation of the genuinely three-dimensional (3D) character of the stagnation process. Modeling NIF implosions is further complicated by the many perturbation sources that have been found to influence integrated implosion performance: flux asymmetries from the surrounding hohlraum, engineering features such as support tents and fill tubes, surface defects and contaminants, and more recently the radiation shadow cast by the fill tube on the capsule. A model including all of these effects, and with adequate resolution, challenges current computing capabilities but has recently become feasible on the largest computers. This paper reviews the status of these multi-effect, 3D simulations of NIF implosions, their comparison to experimental data, and preliminary results on scaling these simulations to the threshold of ignition on NIF.